Perceived needs for support among care home staff providing end of life care for people with dementia: a qualitative study. (14th March 2016) - Vandrevala, T.; Samsi, K.; Rose, C.; Adenrele, C.; Barnes, C.; Manthorpe, J.
Abstract : Objective: The aim of the current exploratory study was to investigate the impact on care home staff when working with people with dementia at the end of life and to explore how they cope with this aspect of their work. With UK policy encouraging death in the place of residence, rather than hospital, more people with dementia are dying in care homes. Method: A qualitative approach was employed; 20 care home staff working in five English care homes were interviewed. Thematic Analysis was used to analyse the data. Results: Care home staff found the external demands on them and difficulties associated with interacting with people with dementia sometimes challenging, stressful and anxiety‐provoking, particularly as residents approached end of life. Emotional aspects of caring for dying residents were sometimes heightened by close attachments with residents and their families. Staff were able to recognise these unmet needs and identified a need for further training and emotional support to manage these stressors. Conclusions: This study revealed rich and complex understandings of the practice dimensions of caring for people with dementia at the end of life and the impact these have on staff. There is a need to develop effective psychosocial interventions that focus on emotional support for care home staff. There will be challenges in providing this in employment settings that are generally low paid, low status, have high turnover and are reliant on temporary or migrant staff, where training is not rewarded, mandatory or culturally valued. Copyright © 2016 John Wiley & Sons, Ltd.